Effects of caffeinated beverage ingestion on salivary antimicrobial proteins responses to acute exercise in the heat - Cheng, Lin; Wang, Hongli; Han, Yanbai (Frontiers in Nutrition, 2022)
Caffeine is commonly used by athletes as an energy supplement, but studies on its effects on salivary antimicrobial proteins (sAMPs) in humans during exercise are rare with ambiguous findings. It is also still controversial whether hot environments affect sAMPs. Using a double-blind, randomized crossover design, we examined 12 endurance-trained male collegiate athletes who completed the following two experiments: a caffeine experiment (CAF) and a placebo experiment (PLA). The participants acutely consumed caffeine-containing (6 mg/kg body weight) sports drink (3 ml/kg body weight) or an equivalent amount of placebo sports drink and subsequently performed cycling exercise for 40 min in the heat (33 ± 0.24°C, 64 ± 2.50% relative humidity) at 50% of maximum output power, maintaining a pedal frequency of 60 rpm. Saliva was collected at 60 min pre-exercise (T–60), the start of exercise (T0), 20 min of exercise (T20), and the end of the exercise (T40), and salivary α-amylase (sAA) and lactoferrin (sLac) were tested. The rating of perceived exertion (RPE) was measured at T0–T40, while core body temperature (Tre) and heart rate (HR) were monitored continuously. Tre, HR, and RPE increased with time during the exercise (p < 0.01), with no difference in Tre and HR between the CAF and PLA (p > 0.05), but RPE was higher in the PLA than in the CAF (p < 0.05). sLac concentrations were significantly higher at T20 and T40 than at T–60 (p < 0.01) and higher at T40 than at T0 and T20 (p < 0.01), with no difference between the CAF and PLA (p > 0.05). Compared with T–60, sAA activity was significantly increased at T0, T20, and T40 (p < 0.01). sAA activity was significantly higher at T40 than at T0 and T20 (p < 0.01), at T20 than at T0 (p < 0.05), and in the CAF than in the PLA (p < 0.01). Heat stress caused by acute exercise in hot environments did not impair the sAMPs parameters of the participants. Instead, the participants showed transient increase in sAA activity and unchanged sLac concentrations. Caffeine may increase salivary markers related to immune response during exercise.